Guardians of the Digital Frontier: Cyberlaw and Privacy Insights - Pitaloka, Vernanda Diah; Purwaningsih, Sri Budi; Fiddina, Irta (Proceedings of The ICECRS, 2023)
In this comprehensive study, we delve into the digital jurisprudence of Cyberlaw and Privacy, examining the robust dataset curated from Lens.org. Employing a refined search strategy, we analyzed journal articles through the keywords "Cyberlaw OR Cyber Law AND Privacy," filtering results by the Subject Law and Document Type Journal Article. The rich dataset revealed a dynamic landscape, showcasing yearly uploads, institutional activity, and global contributors. By meticulously charting the upload trends, active institutions, and prolific countries, our analysis sheds light on the vital intersection of law, technology, and privacy in the virtual realm. This study emphasizes the critical importance of Cyberlaw and Privacy knowledge dissemination for individuals, businesses, and governments in the digital age, fostering a safer online environment.Highlights : Global Digital Legal Landscape Unveiled: Our analysis of Cyberlaw and Privacy publications on Lens.org illuminates a rich tapestry of global legal research, emphasizing the increasing importance of online privacy and cybersecurity in the digital age. Institutions Pioneering Digital Ethics: Highlighting active institutions, we identify key contributors shaping Cyberlaw discourse. Their diverse expertise underscores the multidisciplinary nature of cybersecurity, ranging from law to computer science. Empowering Safer Digital Spaces: Understanding Cyberlaw and Privacy isn't just for academics. It's crucial for everyone navigating the internet. This study emphasizes the pivotal role of legal knowledge in safeguarding online privacy, advocating for informed policies and practices worldwide. Keywords: Cyberlaw, Privacy, Digital Jurisprudence, Online Security, Data Protection